Pronunciation Difficulties for Costa Rican EFL Learners - Pizarro Chacón, Ginneth (2015)
A study was conducted on various aspects which currently affect Costa Rican Spanish speakers when they are learning and practicing the pronunciation of standard English. Based on a review of information and its observation by means of surveys, significant elements are addressed to face the most frequent difficulties when improving pronunciation. Emphasis is given to the fact that since the study focuses on the variant of Costa Rican Spanish, the recommendations given refer to that sociolinguistic situation.